Free Vibration Analysis of Perforated Laminated Composite Square Plates (Journal of University of Babylon for Engineering Sciences, 2018)
This paper presents a study of free vibration of perforated laminate composite plate. The modal characteristics consist of three layers, the material is hard orthotropic composite material, with simply support (SSSS), Clamped boundary (CCCC) and simple clamed conditions (SCSC) are applied at all four edges of the plate.. The natural frequency and mode shape of the plates have been obtained using ANSYS 15. Eight-node isopaprametric layered shell elements (SHELL 281) are employed in the modeling for describing the vibrations of these perforated laminate composite plates. The effect of number of holes, hole area ratio, lamination angles and boundary condition on vibrations are investigated. The convergence study was achieved for numerically and compare with present literature. The results showed that the frequencies of the plate with one hole at the center are different from the perforated plate when maintaining a fixed ratio hole area, as well the lamination angle has a clear effect on the increase and decrease of the fundamental frequency for all the tested cases.